Stand out of our light : freedom and resistance in the attention economy - Williams, James (Philosopher) (Cambridge : Cambridge University Press, 2018)
Former Google advertising strategist, now Oxford-trained philosopher James Williams launches a plea to society and to the tech industry to help ensure that the technology we all carry with us every day does not distract us from pursuing our true goals in life. As information becomes ever more plentiful, the resource that is becoming more scarce is our attention. In this'attention economy', we need to recognise the fundamental impacts of our new information environment on our lives in order to take back control. Drawing on insights ranging from Diogenes to contemporary tech leaders, Williams's thoughtful and impassioned analysis is sure to provoke discussion and debate. Williams is the inaugural winner of the Nine Dots Prize, a new Prize for creative thinking that tackles contemporary social issues. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: Distraction (Psychology); Attention; Interest (Psychology); Information technology -- Social aspects